2016
DOI: 10.1111/joim.12534
|View full text |Cite
|
Sign up to set email alerts
|

Insulin signalling in Alzheimer′s disease and diabetes: from epidemiology to molecular links

Abstract: Abstract. Ribe EM, Lovestone S (University of Oxford, Oxford, UK). Insulin signalling in Alzheimer 0 s disease and diabetes: from epidemiology to molecular links (Key Symposium). J Intern Med 2016; 280: 430-442.As populations across the world both age and become more obese, the numbers of individuals with Alzheimer 0 s disease and diabetes are increasing; posing enormous challenges for society and consequently becoming priorities for governments and global organizations. These issues, an ageing population at r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(60 citation statements)
references
References 111 publications
(156 reference statements)
1
56
0
3
Order By: Relevance
“…Previous research has shown many correlations between inflammation in the brain and neuronal damage [32]. Obesity and insulin resistance are also associated with higher levels of inflammatory biomarkers [33]. …”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown many correlations between inflammation in the brain and neuronal damage [32]. Obesity and insulin resistance are also associated with higher levels of inflammatory biomarkers [33]. …”
Section: Discussionmentioning
confidence: 99%
“…Members of the bone morphogenetic protein family of growth factors have been implicated as crucial modulators of neurogenesis in the adult hippocampus [25, 26] and have been demonstrated to affect amyloid-β-induced neurotoxicity [27, 28] and amyloid plaque burden [29]. In addition, available evidence indicates involvement of insulin and insulin-like growth factor-1 [30] and STAT3 [31] signaling in AD.…”
Section: Discussionmentioning
confidence: 99%
“…This has led to increased interest in the role that insulin might play in the nervous system and it is becoming very clear that there is a strong link between diabetes and Alzheimer's disease (Ribe and Lovestone, 2016). Many of the CNS changes associated with diabetes are similar to those observed in Alzheimer's disease, including increased beta amyloid and tau phosphorylation (Akter et al, 2011).…”
Section: Insulin and The Nervous Systemmentioning
confidence: 99%